Upaya Menurunkan Skala Phlebitis dengan Pemberian Kompres Hangat di RSUD Prof. Dr. Margono Soekardjo Purwokerto - Triyanto, Endang; Handoyo,; Permana, Ryan Hara (Jurusan Keperawatan FIKES UNSOED, 2007)
Intravenous therapy is commonly used to treat patients and it is received through a peripheral cannula by most hospitalized patients. A consequence of intravenous (IV) devices is that risk of nosocomial infection is increased, particularly septicemia. Inflammation, hard vein and thrombophlebitis, and local tenderness are common complication of IV therapy. This can lead to enhanced morbidity and mortality rates. Some treatments to cure phlebitis patients have been done to eradicate phlebitis patients during hospital stay. However, mostly phlebitis treatments have not been standardized as procedure at hospital. Therefore, this study will analyse treatment with sponge water for decreasing phlebitis scale at Margono Soekardjo Hospital. The purpose of the study was to analyse treatment with sponge water for decreasing phlebitis scale at Margono Soekardjo Hospital. This study utilized quasi experimental with one group pre tes and post test design. Of 30 patients at Margono Soekardjo Hospital were involved in this study. Respondents were chosen by purposive sampling method. Criteria of respondents were patients who have 3 days care, 18-80th olds, not performance chronic illness. The analysis of this study uses paired t test. The study show that treatment with sponge water can lead decreasing phlebitis scale. At the first day, score p is 0,000 and the second day is 0,003. There is significant.